Analisa SWOT Kebijakan Poros Maritim Global di Wilayah Kepulauan Riau - Yudilla, Artha; Amri, Pahmi (Nation State: Journal of International Studies, 2020)
Geostrategic and geopolitical positions provide opportunities for Indonesia not only as a global economic path but also an international marine security pathway. Maritime wealth is also a force in Indonesia's maritime diplomacy in the International realm. This is then the basis of the formulated mega project policy to make Indonesia a global maritime axis. But the problem is that so far the Global Maritime Fulcrum policy does not yet have a detailed blueprint for policy implementation in the national state and only focuses on macro discussions in the form of international cooperation discourse that has also not seen significant progress. . This research will try to analyze how the Global Maritime Axis policy is implemented. What are strengths, weaknesses, opportunities, and threats. at the micro level. To be more specific, this research will take a case study in Riau islands which is one of the most strategic maritime areas in Indonesia located in the strait of Malacca. By analyzing how this policy is rationed directly in the micro realm can be a record for governments in formulating better policies in the future.